1984
DOI: 10.1038/jcbfm.1984.57
|View full text |Cite
|
Sign up to set email alerts
|

The Modular Organization of the Pial Arterial System in Phylogeny

Abstract: We have investigated the pial arterial microcircles formed by the consecutive ramifications and anastomoses of minute pial vessels on the surface of the cerebral neocortex in various vertebrate species, representatives of various levels of phylogenic development. We found that the pial arterial microcircles became gradually more complex in the following order: hen < rabbit < cat < dog < monkey. The gradual development of microcircles involves various features in these species: (a) They become forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 13 publications
2
29
0
Order By: Relevance
“…The effect of Paco2 on ECBV (Fig. 1) strongly supports the prominent role of extraparenchymal vascular bed in the vasodilatory adaptation to hypercapnia (Raper et aI., 1971;Mchedlishvili and Kuridze, 1984). Under these circumstances, ECBV, which can increase at the most by 55%, appears to be the main location of the cerebral vascular reserve.…”
Section: Cerebral Blood Volumementioning
confidence: 63%
See 1 more Smart Citation
“…The effect of Paco2 on ECBV (Fig. 1) strongly supports the prominent role of extraparenchymal vascular bed in the vasodilatory adaptation to hypercapnia (Raper et aI., 1971;Mchedlishvili and Kuridze, 1984). Under these circumstances, ECBV, which can increase at the most by 55%, appears to be the main location of the cerebral vascular reserve.…”
Section: Cerebral Blood Volumementioning
confidence: 63%
“…In the case of continuous capillary perfusion, blood flow regulation is under the unique control of vasomotion. This muscular control is located mainly outside the parenchyma itself, in the cere bral arteries, as well as in pial arteries and arterioles (Mchedlishvili and Kuridze, 1984); these vessels, acting as regulators of the cerebral vascular re-serve, determine the flow rate in the brain capillary network. By contrast, if the total capillary network is intermittently perfused, the adaptation of the ce rebral blood flow to high-flow conditions could also be dependent on the opening of previously closed capillaries.…”
mentioning
confidence: 99%
“…1-4 and Table 1). We conjecture, based on comparative studies of pial vasculature (38), that a similar topology is found in higher mammals.…”
Section: Discussionmentioning
confidence: 99%
“…The optical depth of the mea surement in the capillary region is unknown. How ever, because the pial arterioles and venules pene trate tangentially into the cortex (Mchedlishvili and Kuridze, 1984), the reflected light originating from these thick vessels may not include the spectrum of the capillary region.…”
Section: Evaluation Of Present Systemmentioning
confidence: 99%